2020
DOI: 10.2147/ppa.s242336
|View full text |Cite
|
Sign up to set email alerts
|

<p>Treatment Mode Preferences in Psoriatic Arthritis: A Qualitative Multi-Country Study</p>

Abstract: Objective: Qualitative research exploring patient preferences regarding the mode of treatment administration for psoriatic arthritis (PsA) is limited. We report patient preferences and their reasons across PsA treatment modes. Methods: In this global, cross-sectional, qualitative study, interviews were conducted with adult patients with PsA in Brazil, France, Germany, Italy, Spain, the UK, and the US. Patients were currently taking a disease-modifying antirheumatic drug (DMARD). Patients indicated the order an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
(18 reference statements)
3
12
1
Order By: Relevance
“…This survey was conducted through ArthritisPower, a rheumatology-focused patient organization, which may also have led to recruiting bias toward patients experiencing joint pain symptoms over psoriasis-associated symptoms, resulting in overrepresentation of musculoskeletal symptoms. However, compared with other patient preference literature in the rheumatology-based PsA population, the relative symptom burden appears to be in line with other studies [3,12,30,39].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This survey was conducted through ArthritisPower, a rheumatology-focused patient organization, which may also have led to recruiting bias toward patients experiencing joint pain symptoms over psoriasis-associated symptoms, resulting in overrepresentation of musculoskeletal symptoms. However, compared with other patient preference literature in the rheumatology-based PsA population, the relative symptom burden appears to be in line with other studies [3,12,30,39].…”
Section: Discussionsupporting
confidence: 89%
“…We found that most respondents in this study preferred once-daily oral dosing, although mode of administration was not a high priority to many respondents when considering treatment options. The convenience of daily oral dosing often makes it a highly desired mode of administration among patients, according to respondents in this study and previous literature [ 12 , 39 ]. This preference was consistent both in patients with bDMARD experience and in patients without bDMARD experience, indicating that familiarity with parenteral administration used in bDMARDs did not change preferences for oral administration.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Reports indicate that patients prioritize biologic safety, followed by efficacy. It should be noted that some studies indicate that, in up to 40% of cases, treatment preferences stand to benefit from communication with providers [ 30 ]. One of the positive findings of our study is that nearly all patients experienced discussion over second-line treatment (i.e., biologics) with their providers.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriatic arthritis disease characteristics are shown in Table 2. The median duration of skin symptoms was 19 years (IQR, 10-34), the median duration of joint symptoms was 12 years (IQR, 8-21), and the median time since PsA diagnosis by a physician was 8 years (IQR, [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Peripheral and axial PsA symptoms were present in 97% and 52% of patients, respectively.…”
Section: Patient Characteristicsmentioning
confidence: 99%